Examining the nuclear mass surface of Rb and Sr isotopes in the A≈104 region via precision mass measurements - Mukul, Ish; Andreoiu, C.; Bergmann, J.; Brodeur, M.; Brunner, T.; Dietrich, K. A.; Dickel, T.; Dillmann, I.; Dunling, E.; Fusco, D.; Gwinner, G.; Izzo, C.; et al. (Physical review, 2021)
Background: The neutron-rich A≈100, N≈62 mass region is important for both nuclear structure and nuclear astrophysics. The neutron-rich segment of this region has been widely studied to investigate shape coexistence and sudden nuclear deformation. However, the absence of experimental data of more neutron-rich nuclei poses a challenge to further structure studies. The derivatives of the mass surface, namely, the two-neutron separation energy and neutron pairing gap, are sensitive to nuclear deformation and shed light on the stability against deformation in this region. This region also lies along the astrophysical r-process path, and hence precise mass values provide experimental input for improving the accuracy of the r-process models and the elemental abundances.
Im Titel wird approximate to als Zeichen dargestellt
Gesehen am 29.07.2021